2016
DOI: 10.1016/j.drugpo.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

“Can’t you initiate me here?”: Challenges to timely initiation on antiretroviral therapy among methadone clients in Dar es Salaam, Tanzania

Abstract: Background Despite dramatic improvement in antiretroviral therapy (ART) access globally, people living with HIV who inject drugs continue to face barriers that limit their access to treatment. This paper explores barriers and facilitators to ART initiation among clients attending a methadone clinic in Dar es Salaam, Tanzania. Methods We interviewed 12 providers and 20 clients living with HIV at the Muhimbili National Hospital methadone clinic between January and February 2015. We purposively sampled clients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Lack of conformity leads to double stigma for HIV-positive key populations: HIV-positive key populations face marked discrimination related to their life-style. MSM, PWID and sex-workers all do not conform to social norms and as a result are morally judged and discriminated against by others [50, 54, 64, 80, 88]. This discrimination is often worse than that experienced by those who are HIV-positive alone [50, 54, 64] and may cause psychological distress [50, 64], compounded by criminalization of MSM and sex-work in several African settings [50, 54, 88].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of conformity leads to double stigma for HIV-positive key populations: HIV-positive key populations face marked discrimination related to their life-style. MSM, PWID and sex-workers all do not conform to social norms and as a result are morally judged and discriminated against by others [50, 54, 64, 80, 88]. This discrimination is often worse than that experienced by those who are HIV-positive alone [50, 54, 64] and may cause psychological distress [50, 64], compounded by criminalization of MSM and sex-work in several African settings [50, 54, 88].…”
Section: Resultsmentioning
confidence: 99%
“…MSM, PWID and sex-workers all do not conform to social norms and as a result are morally judged and discriminated against by others [50, 54, 64, 80, 88]. This discrimination is often worse than that experienced by those who are HIV-positive alone [50, 54, 64] and may cause psychological distress [50, 64], compounded by criminalization of MSM and sex-work in several African settings [50, 54, 88]. As a result, key-populations often have very limited support [50, 64, 76, 88] and for PWID, even with excellent support, drug addiction may trump any consideration of health status [56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Thus, there is a clear need to manage substance use disorders and the barriers to early initiation of anti-retroviral treatment in "Test and Treat" programs for people living with HIV, who use drugs.…”
mentioning
confidence: 99%
“…25 Delays in CD4 testing and receiving results have been shown to hinder early linkage to HIV care and treatment. 26 The ISPP provided CD4 and viral load testing at the time of diagnosis to expedite the process of testing and getting results. However, our evaluation demonstrated that the time to link to care was not significantly improved between those who consented to blood work and those who declined within the intervention group.…”
mentioning
confidence: 99%